ANALISIS FAKTOR YANG BERKAITAN DENGAN KASUS GIZI BURUK PADA - Budi F. Wahyudi; Sriyono Sriyono; Retno Indarwati (Universitas Airlangga, 2014)
Introdduction: The purpose of this research was to describe the factors related to cases of malnutrition on toddlers at Sampang 2014.Methods: The research is descriptive research that uses cross sectional approach. Population research totaling 21 mothers who have toddlers malnutrition. Factors that are examined is mother’s education level, mother’s occupation, history of low birth weight, family income, mother’s knowledge of nutrition, and infectious diseases, exclusive breastfeeding status and immunization status. Data analysis using a technique descriptive analysis manually (frequency distribution and percentage ).Result: The results showed more than half the number of the respondents have low education levels 64,8%, more than half the number of the respondents not working 58,8%, a small percentage of the respondents have a good knowledge about nutrition 23.5%, the majority of respondents have an income less 88,2%, most of those born with the condition normal 88,2%, Most toddlers are exposed to infectious diseases 76.5%, more than half the number of babies given breastfeeding exclusively 58,8%, most toddlers have the immunization status of 76.5%, more than half the number of toddlers begin to get its nutrition value status improved 64,7%.Conclusion: Family income less, history of infectious diseases, low levels of education and mothers who do not work are factors of risk have the largest distribution on this research. Health promotion about nutrition can be used to increase knowledge as well as the necessity of evaluating the toddler's mother at least once a month to see the effectiveness of the actions and programs that are already done